Stem Cell Statute in Jordan: Leading the Way - Al-Tabba’, Amal; Dajani, Rana; Al-Hussaini, Maysa (Frontiers in Genetics, 2020)
The use of stem cells in research has caused much controversy and ethical dilemma. The primary source of stem cells is human embryos, a source which has been confronted with objections based on ethical, moral and religious positions. Jordan has passed the first of its-kind Statute in the region, aiming at regulating the use of stem cells both for therapeutic and research purposes. The Statute adopted a regulatory approach between the restrictive and intermediate. The Statute, however, pays more attention to stem cell banking in many of its articles. Many critical aspects in regulating stem cell research activities are overlooked. This is including but not limited to the process of informed consent, protecting privacy, maintaining confidentiality, the need for a national entity responsible for regulating embryonic stem cell (ESC) research, and requirements of monitoring activity. The authors recommend further review of the current Statute in light of the deficiencies discussed so as to develop a more comprehensive and coherent Statute.